On switchbox routing algorithm - Vardan A. Manukyan (Изд-во НАН РА)
We present new switchbox routing algorithm that consider the characteristic of net crossings. The routing strategy is based on parallel bubble sorting technique. Non-Manhattan wires as well as overlapping wires are introduced. Preliminary results show that a class of switchbox routing problems can be routed by using smaller overall interconnection length than the Manhattan models provide.
Keywords: Science; Mathematics; Algorithm